Kombinasi Biopestisida Formulasi Bacillus subtilis BNt8 dan Pestisida Nabati untuk Pengendalian Penyakit Hawar Daun Bipolaris maydis pada Jagung - Djaenuddin, Nurasiah; Suriani, Suriani; Talanca, Andi Haris (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2018)
Maydis leaf blight disease caused by Bipolaris maydis can attack corn plants in the vegetative and generative phase and can reduce yield up to 70%. Biological control of plant diseases with the use of biopesticides alone or in combination with other botanical materials can be efficient because it is easy to obtain, cheaper price, also environmentally friendly. The objective of the study was to obtain a combination of B. subtilis formulation with a botanical pesticide which has the potential to control the growth and development of maydis leaf blight. In addition to this, we also observed the effect of the application of the combination of botanical pesticides and B. subtilis formulation on plant growth. The study was conducted on February till June 2016 at the Plant Pathology Laboratory of ICERI with a complete randomized design and the Bajeng Experimental Farm using a randomized block design. In vitro testing, the treatment with vegetable pesticide of clove leaf extract gave better results in suppressing B. maydis. Similarly, in field testing, the application of B. subtilis formulation combined with clove leaf extract also gave a better effect in suppressing the development of maydis leaf blight disease and increasing yield. Applications of B. subtilis formulation can suppress maydis leaf blight disease by up to 13% and potentially increase yield by 26%.